The Effect of miRNA-Modified Exosomes in Animal Models of Spinal Cord Injury: A meta-Analysis - Hu, Mengdie; Cao, Zhidong; Jiang, Dianming (Frontiers in Bioengineering and Biotechnology, 2022)
Background：Spinal cord injury (SCI) is currently not completely curable. Exosomes have been widely used in preclinical studies of spinal cord injury. Here, in this meta-analysis, we focused on evaluating the overall efficacy of therapies based on miRNA-modified exosomes on functional recovery in animal models of SCI. Methods：PubMed, Embase and Web of Science library databases were searched. Relevant literature was included, and the random effects model was used to assess the overall effect of the intervention. Risk of bias (ROB) was assessed using the ROB tool of the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE). R version.1.1 software and Review Manager software were used for meta-analysis. Results：A total of 11 preclinical studies were included. The meta-analysis revealed that miRNA-modified exosome therapy was effective in improving motor function scores compared with exosomes alone or control therapy (standardized mean difference: 4.21; 95% confidence interval: 3.39 to 5.04). There was significant asymmetry in the funnel plot, and trim-and-fill analysis revealed four unpublished studies of motor scores. The quality of all included studies was evaluated with SYRCLE’s ROB tool. The SCI model, administration time and dose had an impact on the effect of the treatment. Conclusion：MiRNA-modified exosomes have shown great potential in the treatment of SCI. Moreover, the efficacy of miRNA-modified exosomes was superior to that of exosomes alone.